Experimentally supported computational method for the optimal design selection of 3D printed fracture healing implant geometries - Lehder, Eric Federico (2023)
The development of AM technologies has brought about very promising opportunities in the field of tissue regeneration, especially due to the design freedom they enable. However, the tools and procedures needed to enable medical designers to make use of these revolutionary technologies still need to be developed. In particular, design tools to make implants with optimal geometries for tissue regeneration and procedures to manufacture and test such implants need to be developed to enable the adoption of these technologies by medical designers and biologists designing implants. This thesis aims to address this need.